Detecting Apoptosis in Human Kidney (HK-2) Cells. - Raupach, Elizabeth A. (My University, 2009)
Identification of apoptosis and quantification of cell death can be done with a combination of morphological criteria and analysis of DNA. A newer method utilizes an in situ approach to identify cells with damaged DNA due to apoptosis. We established conditions to grow monolayers of HK-2 cells in 8 well chambered slides and established criteria for efficient labeling using permeability agents and fixation procedures.
Color poster with text, images, and diagrams.
Keywords: Apoptosis--Diagnosis; Cell death--Measurement; Kidneys--Diseases--Diagnosis; Posters